Implementation of sharia principles in the insurance industry in Indonesia: Systematic Literature Review - Isnaini Hikmah Hidayah; Taufiqur Rahman (Universitas Islam Negeri (UIN) Walisongo Semarang, 2025)
Purpose - Aims to examine in depth the implementation of sharia principles in the insurance industry in Indonesia. The main focus is to evaluate the extent to which principles such as monotheism, justice, ta'awun, and cooperation are implemented through sharia contracts such as tabarru', tijarah, mudharabah musytarakah, and wakalah bil ujrah in sharia insurance practices. Method - The method used in this study is Systematic Literature Review (SLR). Data were collected from 500 articles filtered through Google Scholar with the keywords